HRM Practices and Their Effect on Employees’ Job Involvement in Nepalese Public Financial Institutions - Basnet, Bhupindra Jung; Neupane, Rabindra Kumar; Kandel, Madan (Nepal Journal of Multidisciplinary Research, 2025)
Background: Human resource management (HRM) play a crucial role in shaping employee attitudes and behaviors in the workplace. Job involvement, which reflects an employee’s psychological identifications with their job, is influenced by various HRM practices, including SE, TD, PA, PR, COM, and EM. Understanding the impact of these practices on job involvement is essential for organizations seeking to enhance engagement and productivity. Objective: This study aims to examine the effect of HRMP on employees’ job involvement. Specifically, it investigates the influence of SE, TD, PA, PR, COM, and EM on employees’ job involvement. Methods: A combination of research designs have been applied that was descriptive and causal-comparative. The study utilized a sample of 340 employees. SEM was applied to analyze the relationship between HRMP and JI. Findings: The results indicate that HRMP and JI. Among the HRM practices studied, TD, COM, and EM significantly and positively influenced job involvement. However, SE, PA, and PR did not show a significant impact on job involvement. Conclusion: HRM practices contribute to job involvement by offering skill, enhancement program, assessing responsibilities, and fostering an open communication system. Organizations should prioritize training and development, effective communication, and employee empowerment to improve job involvement. Novelty: This study provides empirical evidence on the differential impact of various HRM practices on job involvement. Unlike previous studies that consider HRMP as a whole, this research highlights the specific practices that significantly influence job involvement, offering valuable insights for HR managers and policymakers.